Clofarabine, idarubicin, and cytarabine (CIA) as frontline therapy for patients ≤60 years with newly diagnosed acute myeloid leukemia. Issue 11 (9th September 2013) - Nazha, Aziz; Kantarjian, Hagop; Ravandi, Farhad; Huang, Xuelin; Choi, Sangbum; Garcia‐Manero, Guillermo; Jabbour, Elias; Borthakur, Gautam; Kadia, Tapan; Konopleva, Marina; Cortes, Jorge; Ferrajoli, Alessandra; et al.
<x xml:space="preserve">Abstract</x> Clofarabine is a second generation nucleoside analogue with activity in adults with acute myeloid leukemia (AML). A phase I trial of clofarabine, idarubicin, and cytarabine (CIA) in relapsed and refractory AML had shown an overall response rate (ORR) of 48%. To explore this combination further, we conducted a phase II study of (CIA) in patients with newly diagnosed AML ≤60 years. Patients ≥18–60 years with AML and adequate organ function were enrolled. Induction therapy consisted of clofarabine (C) 20 mg m−2 IV daily (days 1–5), idarubicin (I) 10 mg m−2 IV daily (days 1–3), and cytarabine (A) 1 g m−2 IV daily (days 1–5). Patients in remission received up to six consolidation cycles (C 15 mg m−2 × 3, I 8 mg m−2 × 2, and A 0.75 g m−2 × 3). Fifty‐seven patients were evaluable. ORR was 79%. With a median follow up of 10.9 months, the median overall survival (OS) was not reached, the median event‐free survival (EFS) was 13.5 months. Most toxicities were ≤grade 2. Four week mortality was 2%. In subgroup analysis, patients ≤40 years had better OS (P = 0.04) and EFS (P = 0.04) compared to patients >40 years. Compared to historical patients treated with idarubicin and cyarabine (IA), the OS and EFS were significantly longer for CIA treated patients. In multivariate analysis, CIA retained its favorable impact on OS compared to IA. Thus, CIA is an effective and safe therapy for patients ≤60 years with newly diagnosed AML. Am. J. Heamtol. 88:961–966, 2013. © 2013 Wiley Periodicals, Inc.